2018
DOI: 10.1186/s13071-018-3012-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic activity of chicory (Cichorium intybus) and its natural bioactive compounds in livestock: a review

Abstract: Increasing drug resistance in gastrointestinal (GI) parasites of livestock and concerns about chemical residues in animal products and the environment are driving the development of alternative control strategies that are less reliant on the use of synthetic drugs. An increasingly investigated approach is the use of bioactive forages with antiparasitic properties as part of the animal’s diet (nutraceuticals) or as potential sources of novel, natural parasiticides. Chicory (Cichorium intybus) is a multi-purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 147 publications
(177 reference statements)
1
42
0
1
Order By: Relevance
“…Inhibitory effects of chicory on parasitic nematodes in ruminants and mono-gastric livestock is well documented and convincing evidence from in vitro studies suggest that SL are the primary compounds responsible for this inhibition 40 . Anthelmintic activity of chicory was demonstrated in an in vitro egg hatch inhibition assay against Haemonchus contortus .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Inhibitory effects of chicory on parasitic nematodes in ruminants and mono-gastric livestock is well documented and convincing evidence from in vitro studies suggest that SL are the primary compounds responsible for this inhibition 40 . Anthelmintic activity of chicory was demonstrated in an in vitro egg hatch inhibition assay against Haemonchus contortus .…”
Section: Discussionmentioning
confidence: 98%
“…Aside from SL, numerous other bioactive compounds have been reported from chicory such as hydroxycinnamic acids with e.g. insecticidal and acaricidal effects 40,46,47 . Such investigations would optimally be done by bioassay guided fractionation and identification of active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Sesquiterpenes are known for their anthelmintic properties against GI nematodes like Haemonchus contortus and Ascaris suum (Foster et al ., 2011; Williams et al ., 2016). Inulin also causes in vivo changes of parasite communities, but its anthelmintic mechanism of action cannot be fully explained (Jensen et al ., 2011; Peña-Espinoza et al ., 2018). In our study, the aqueous extract of I. helenium showed strong ovicidal and larvicidal effects, with a maximum egg-hatching-reduction percentage of 100 (±0), and an LC-50 value of 0.041 mg/ml (95% CI 0.010–0.164).…”
Section: Discussionmentioning
confidence: 99%
“…C. intybus has attracted interest owing to its anthelmintic effects on gastrointestinal (GI) nematodes in monogastrics and ruminants [ 60 ]. Scientific evidence has demonstrated that chicory-rich diets can potently decrease infections with GI abomasal nematodes in cattle and sheep in vivo [ 60 ]. For this reason, compounds 1 – 3 have been tested for their anthelmintic effects on Caenorhabditis elegans .…”
Section: Biological Activitiesmentioning
confidence: 99%